Clinical and pharmacogenetic determinants of 5-fluorouracyl/leucovorin/irinotecan toxicity: Results of the PETACC-3 trial. (August 2018) - Tejpar, Sabine; Yan, Pu; Piessevaux, Hubert; Dietrich, Daniel; Brauchli, Peter; Klingbiel, Dirk; Fiocca, Roberto; Delorenzi, Mauro; Bosman, Fred; Roth, Arnaud D.
Abstract: Purpose: Irinotecan (CPT-11) in combination with 5-fluorouracil (5FU) is widely used in the treatment of colorectal cancer. We assessed potential clinical variables that may predict toxicity and more specifically the role of UGT1A1 polymorphisms associated with irinotecan toxicity. We used data from the PETACC3 trial, which randomised patients in adjuvant setting to 6 months of leucovorin (LV) and 5FU (LV5/FU2) or LV5/FU2 + irinotecan. Patients and methods: Clinical and toxicity data were available for 2982 patients, DNA was available for 1200 (40%) of these patients. We genotyped the polymorphisms UGT1A1*28 and UGT1A1-3156G > A. Risk factors for neutropenia and diarrhoea were assessed by univariable and multivariable analyses. Results: In univariable analysis, UGT1A*28 genotype was associated with an increased incidence of grade III–IV neutropenia (incidence: 44% versus 26%; odds ratio [OR]: 2.3; 95% confidence interval [CI]: 1.4–3.7). In multivariable analysis, the most important predictors (ordered in terms of contribution to R 2 ) were baseline neutrophil count (OR for 1-unit (10 9 /l) decrease: 1.8, 95% CI: 1.3–1.7), female sex (OR: 1.8, 95% CI: 1.1–3.0), body surface area (OR for 0.1-unit increase: 0.8, 95% CI: 0.7–1.0), UGT1A1 (OR: 2.8, 95% CI: 1.6–5.0), age (OR per 10 years: 1.3, 95% CI: 1.1–1.6) and poor performance status (OR: 1.6, 95% CI: 1.0–2.6). The main predictors for grade IV neutropenia were sex, age, performance score and UGT1A1. The main predictors for diarrhoea were sex and age. Conclusions: We found that a complex of risk factors is involved in the development of toxicity, including UGT1A1. Parameters that are readily available in clinical practice, notably sex, age and performance status, are stronger predictors than the UGT1A1*28 genotype. Further studies beyond the UGT1A1*28 genotype are needed to fully understand the determinants of toxicity risk, notably in females. Highlights: UGT1A*28 genotype was associated with an increased incidence of grade III–IV neutropenia in colorectal cancer (CRC) patients treated with 5-fluorouracyl/leucovorin/irinotecan. But more important predictors were baseline neutrophil count, sex and body surface area; less important predictors were age and poor performance status. The main predictors for diarrhoea were sex and age.